CRIMINAL LIABILITY OF HOLDING COMPANIES FOR ENVIRONMENTAL CRIMES COMMITTED BY SUBSIDIARIES - Arman Candra; Fitri Rafianti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The structure of multinational corporations has created fundamental juridical challenges regarding criminal liability. The principle of separate legal personality has traditionally insulated holding companies from liability for environmental crimes committed by their subsidiaries, notwithstanding the parent company's dominant operational and economic control. This research examines how various legal systems address this accountability issue through doctrines such as piercing the corporate veil, vicarious liability, and systemic fault models. Furthermore, this study analyzes the effectiveness of the Indonesian legal framework, specifically the Law on Environmental Protection and Management (UUPPLH, Article 116) and Supreme Court Regulation No. 13 of 2016 (Articles 4(2) and 6), while identifying the causes of implementation gaps. Comparative analysis reveals a global evolution from the restrictive identification doctrine toward a pragmatic organizational fault model. It is found that Indonesia's legal framework is de jure adequate, having adopted functional liability (UUPPLH) and organizational liability (Perma). However, the key finding highlights the absence of de facto jurisprudence due to structural barriers, particularly evidentiary challenges and institutional capacity. In conclusion, this research recommends the adoption of a hybrid prosecution model combining the functional instruments of the UUPPLH and the organizational instruments of Perma 13/2016 as an effective solution to combat holding company impunity.